Adjuvant treatment patterns and outcomes in patients with stage IB-IIIA non-small cell lung cancer in France, Germany, and the United Kingdom based on the LuCaBIS burden of illness study. (October 2018) - Chouaid, Christos; Danson, Sarah; Andreas, Stefan; Siakpere, Obukohwo; Benjamin, Laure; Ehness, Rainer; Dramard-Goasdoue, Marie-Hélène; Barth, Janina; Hoffmann, Hans; Potter, Vanessa; Barlesi, Fabrice; Price, Mark; et al.
Highlights: This study describes treatment patterns associated with resected NSCLC. Less than half of the patient population (48%) received adjuvant systemic therapy. Approximately 40% of patients did not complete their planned course of treatment. The 25th percentile of disease-free survival and overall survival were 13.2 and 31.2 months respectively. 33% of the patients had disease recurrence during the follow-up period. Abstract: Objectives: To inform health-technology assessments of new adjuvant treatments, we describe treatment patterns in patients with complete resection of stage IB-IIIA non-small cell lung cancer (NSCLC) in France, Germany, and the United Kingdom (UK). Materials and methods: Data were collected via medical record abstraction. Patients were aged ≥18 years with completely resected stage IB-IIIA NSCLC, diagnosed between 01 January 2009 and 31 December 2011. Median follow-up was 26 months. Adjuvant treatment patterns and clinical outcomes were summarized descriptively. Results: Among the 831 patients studied, 239 (29%) had stage IB disease, 179 (22%) had stage IIA disease, 165 (20%) had stage IIB disease, and 248 (30%) had stage IIIA disease. Adjuvant systemic therapy was received by 402 patients (48.4%), (France, 61.8%; Germany, 51.9%; UK, 33.4%). Use of adjuvant therapy increased with increasing stage of disease. Cisplatin/vinorelbine and carboplatin/vinorelbine were the most frequently prescribed adjuvant regimens. Median disease-free survival was 48.0 months (95% confidence interval [CI] 42.3–not estimable); the 25th percentile was 13.2 months (95% CI, 11.0–15.3). 204 patients (24%) died during the follow-up period. The median overall survival was not reached, the 25th percentile was 31.2 months (95% CI 26.8–36.0 months). 272 patients (33%) had disease recurrence during the follow-up period. For 86 of those patients, the first recurrence was local or regional with no distant metastasis and 14 had further progression to metastatic disease during the follow-up time. For the other 186 patients, the first recurrence involved distant metastases. A total of 200 patients had metastatic disease at any time during study follow-up. Conclusions: Less than half the patients with stage IB-IIIA NSCLC in this observational study received adjuvant systemic therapy. A high rate of first recurrence with distant metastatic disease was observed, emphasising the need for more effective systemic adjuvant therapies in this population.